EXPLOITATION OF PHYCOBILIPROTEINS SPECTRAL PROPERTIES AS AN INDICATOR OF HEAVY METAL TOXICITY - M. AYYA RAJU; K. HEMA LATHA; S. D. S. MURTHY (The Bioscan, 2011)
Exposure of intact cells of Spirulina to silver ions (5-15 μM) caused decrease in the phycocyanin absorption and loss in the phycocyanin fluorescence emission indicating the altered energy transfer from phycocyanin to chlorophyll a under in vivo conditions. The in vitro measurements of spectral properties of phycobilisomes isolated from silver treated cells, clearly demonstrated that phycobilisome energy transfer is the major target for silver action. Thus phycocyanin is the major susceptible pigment protein for silver ion action which is evidenced from the decrease of fluorescence emission of phycocyanin.